Effect of selection for pollen grain size on various traits in common bean - Montes Rojas, C; White, Jeffrey W. (1996)
Selection among microgametophytes usually exploits variation in pollen grain germination. Studies of variation in pollen grain size in common bean (Phaseolus vulgaris L.) suggested that selection for size might lead to changes in sporophytic traits. To determine whether microgametophytic selection based on size would affect pollen grain size in subsequent generations or sporophytic traits that were correlated with pollen grain size, pollen grains from three crosses were separated into two size categories by sieving and then used to pollinate cv. Diacol Calima. Selection resulted in changes in pollen grain diameter for pollen from F1, F2 and F3 plants for all crosses. In vitro germination indicated no differences between vigor of large and small grains, but extraction and sieving reduced germinability. F1 seed from two of the crosses with size-selected pollen varied in weight according to pollen grain size, but in subsequent generations, the effect disappeared. Both size categories of selected pollen resulted in F2 progeny with reduced numbers of seeds per pod as compared to controls, suggesting that the size selection process may have resulted in indirect selection for traits reducing seed set. The overall results suggested that genes determining pollen grain size in bean have little or no effect on sporophytic traits such as seed size and seed yield.